Real world telehealth delivery of an evidence based self-management education program for people with epilepsy and cognitive comorbidity - Kiriakopoulos, Elaine T.; Kaden, Sarah J.; Sackett, Lisa P.; Quigley, Maureen T.; Dawson, Trina; DeMuro, Laura; Giordano, Kathryn E.; DeNaples, Jessica; Olenec, Meredith E.; Jennings, Stephanie; Burhanuddin, Ambereen; Harris, Joanne; et al. (Frontiers in Neurology, 2025)
IntroductionCognitive dysfunction is prevalent in epilepsy, and is associated with decreased quality of life. HOme Based Self-management and COgnitive Training CHanges lives (HOBSCOTCH) is an evidence-based self-management program designed for people with epilepsy and comorbid subjective cognitive dysfunction. This project examines the delivery of HOBSCOTCH outside of the research setting as it translates from science to service.MethodsPeople with epilepsy and subjective cognitive dysfunction (n = 205) enrolled in the HOBSCOTCH program over an 11-month period (3/11/24–2/12/25) and completed pre-and post-self-report assessments in which demographics, perceived cognition (Everyday Memory Questionnaire-Revised), quality of life (Quality of Life in Epilepsy-10), shared decision-making (CollaboRATE), and program satisfaction were measured.ResultsAfter completion of the 8-week HOBSCOTCH education program with a Cognitive Coach, participant quality of life and subjective cognition both significantly improved (p < 0.001). Program satisfaction was high, as was shared decision-making.DiscussionHOBSCOTCH Cognitive Coaches deliver a participant-driven one-on-one education program by telehealth, which empowers people with epilepsy to manage their disease and related cognitive symptoms to improve quality of life. Ensuring this low risk behavioral intervention addressing cognitive challenges and quality of life is broadly available is paramount to improving meaningful supports for people with epilepsy.